The influence of resistance exercise with emphasis on specific contractions (concentric vs. eccentric) on muscle strength and post-exercise autonomic modulation: a randomized clinical trial - Mariana O. Gois (Revista Brasileira de Fisioterapia, 2014)
Background: Compared to eccentric contractions, concentric contractions result in higher cardiovascular stress. However, we do not know how these two types of contractions influence cardiac autonomic modulation during the post-exercise recovery period. Objective: to compare the effect of resistance training that is performed with concentric vs. eccentric emphasis on muscle strength and on post-exercise recovery which was assessed by examining heart rate variability (HRV), for the knee extensor muscle group in young healthy adults. Method: For this study, 105 men between 18 and 30 years of age were randomized into 4 groups: concentric control (CONCC), eccentric control (ECCC), concentric training (CONCT) and eccentric training (ECCT). The CONCC and ECCC groups underwent one session of resistance exercise (RE) using the knee extensor muscle group (3 sets of 1 repetition at 100% of the maximal repetition [1MR]) and the CONCT and ECCT groups performed 10 training sessions. The HRV was analyzed at baseline and across four recovery periods (T1, T2, T3 and T4). Results: The ECCT group exhibited increased muscle strength at the end of the study. Regarding cardiac autonomic modulation, the CONCC and ECCC groups exhibited increases in overall variability (SDNN and SD2) at T1 compared to baseline, and the ECCT group demonstrated increases in variables reflecting vagal modulation and the recovery process (RMSSD, SD1 and HF [ms2]) at T1, T2 and T4 compared to baseline. Conclusions: Resistance training with emphasis on eccentric contractions promoted strength gain and an increase in cardiac vagal modulation during recovery compared to baseline.